Reasons and Influence of the Registration System on the Chinese Securities Market - Wang Wenqi (SHS Web of Conferences)
The Chinese securities market has evolved significantly over the past several decades, marked by numerous reforms. Among these, the recent introduction and pilot implementation of the registration system stands out as a crucial change. This reform is designed to foster a healthier market environment by streamlining the listing process and improving transparency within the market. However, the registration system has encountered numerous challenges and resistance during its implementation, leading to setbacks in its advancement. This study seeks to investigate the factors contributing to the challenges encountered by the registration system in China’s securities market, as well as its implications. The research analyzes these obstacles through the lenses of policy frameworks, transparency in information disclosure, and the safeguarding of investor rights, while also assessing their effects on the overall securities market. The research finds that the obstacles to the registration system have had multiple impacts on China’s securities market in terms of trading volume, corporate financing, investor behavior, and market confidence. This article assesses the effects on the securities market and explores possible future policies, with the goal of offering robust support for the sustainable growth of China’s securities market.